Performa Produksi Dan Konsumsi Sumber Energi Negara-Negara Dunia Pada Tahun 2001-2022 - Hasbi Sidik; Fitri Juliana Sanjaya; Fahmi Tarumanegara (Terekam Jejak Publisher, 2024)
The need for energy is an inseparable part of the development states. However, dynamics of energy accumulation activities continually occur in various energy sources such as petroleum, refined oil, coal, natural gas, and electrical energy. This research aims to describe a variety performance of production and consumptions in several countries. Using a quantitative approach with descriptive statistical analysis in 43 countries, it argues that there is no one dominat country producing and consuming in all types of energy sources. Moreover, each countries alternately dominates different types of energy. Finally, United States of America and China always exist in the 5 largest in distinctive energy resources.